Improvement of cavitation erosion characteristics of the centrifugal inducer stage with the inducer bush - Tkach, Pavlo; Yashchenko, Andrii; Gusak, Oleksandr; Khovanskyy, Sergey; Panchenko, Vitalii; Grechka, Iryna (Eastern-European Journal of Enterprise Technologies, 2018)
The impact of the inducer bush, which is a stator bush with longitudinal straight grooves installed over the inducer in the model centrifugal stage on its performance, was studied. A physical experiment was performed with the use of the experimental design techniques to solve the problem of geometrical parameter optimization of the stator bush with longitudinal straight grooves in the multi-factorial problem regarding the improvement of cavitation erosion characteristics of the centrifugal inducer stage using the inducer bush. The frequency spectrum of excited oscillations of the studied centrifugal inducer stage caused by cavitation was determined in order to use the cavitation erosion resistance parameter as an optimization parameter. The optimal dimensions of the inducer bush of the studied centrifugal inducer stage were experimentally determined: Z=32, b=14, l1=20, and l2=20. This data allowed us to improve the cavitation erosion resistance of the centrifugal inducer stage without changing its overall dimensions and deteriorating head and power characteristics. An additional physical experiment was performed using an alternative method for determining the cavitation and erosion characteristics in order to confirm the results obtained in the study due to inducer bushes installed in the centrifugal inducer stage. The use of inducer bushes as a part of the centrifugal inducer stage was mainly intended to improve the centrifugal stage cavitation performance. This study proposes to use this part to overcome the negative effects of cavitation erosion. The possibility of such use was confirmed and research and methodological design recommendations for inducer bushes as part of the centrifugal inducer stage were developed. The installation of the improved first centrifugal stages with inducer bushes in the existing centrifugal pumps will increase the operating time to failure, which is relevant for all industries where centrifugal pumps are used.